Examining the relationship between organisational justice and organizational commitment with perceived organisational support of the Malaysian high performance school sports developmental programme (SPTS) volunteer coaches - Ooi, Cheng Lee; Yusof, Aminuddin; Soh, Kim Geok; Omar, Zoharah (Human Resource Management Academic Research Society, 2017)
This study aims to examine the relationship between organisational justice and organizational commitment with perceived organisational support of the Malaysian High Performance School Sports Developmental Programme (SPTS) volunteer coaches, in an organisation sponsored volunteerism at grass root sports development level. A cross-sectional correlation research mail survey was conducted. Data were analysed by using IBM SPSS statistics software and structural equation modelling with AMOS. Findings showed that interpersonal justice related positively with affective commitment but negatively with continuance commitment; while, distributive justice was only linked to normative commitment. All four dimensions of organisational justice except procedural justice were associated with perceived organisational support. Perceived organisational support relates only to normative commitment. Moreover Organisation Support Theory, under current research, is suggested to contextualise and resolve their conflicting dual roles as a teacher by contract and as a volunteer coach by assignment within the organisation. Besides, it is essential to strengthen the Sports Officers’ capabilities and abilities in volunteer sports management in order to achieve Malaysia’s aim for sports excellence. Future in-depth research is recommended for a better understanding of the subject matter.